Understanding Chinese Culture Philosophy, Religion, Science and Technology (Springer Singapore, 2018)
Promoting cultural understanding in a globalized world, this text is a key tool for students interested in further developing their understanding of Chinese society and culture. Written by a team of experts in their fields, this book provides a survey of Chinese culture, delving deeper into areas such as Chinese philosophy, religion, politics and education. It offers the reader a wide range of essential facts to better understand contemporary China through its history and cultural background, touching on key areas such as the development of science and technology in China, as well as the country's economy and trade history, and is a key read for scholars and students in Chinese Culture, Sociology and Politics.